Coincidence Point and Common Fixed Point Theorems for Generalized Kannan Contraction on Weakly Compatible Maps in Generalized Complex Valued Metric Spaces - Inchan, Issara (Communications in Mathematics and Applications, 2022)
In this work, we study the generalized complex valued metric space for some partial order relation and give some example. Then we established and proved a uniqueness of coincidence point and uniqueness of common fixed point theorems with satisfy weakly compatible for generalized some contraction. The results extend and improve some results of Elkouch and Marhrani [8], and Abbas and Jungck [1].